2023
DOI: 10.3390/plants12040942
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Resistance of Cowpea Vigna unguiculata Control Megalurothrips usitatus Mediated by Jasmonic Acid or Insect Damage

Abstract: Vigna unguiculata is a vital vegetable crop in Southeast Asia, and Megalurothrips usitatus can cause huge damage to this crop. Enhancing the resistance of V. unguiculata against M. usitatus is a promising way to protect this crop; however, there is limited information regarding the mechanism underlying the resistance of V. unguiculata against M. usitatus. Here, a behavior assay was performed to explore the resistance of V. unguiculata against M. usitatus after insect damage or treatment by jasmonic acid (JA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…The increase in ABA may also be induced by water loss resulting from M. usitatus, as ABA is also an indicator of water stress. Li et al [26] have shown that defensive resistance of cowpea control M. usitatus is mediated by JA insect damage. However, there was no significant difference in SA content between treatments.…”
Section: Usitatus Altered Stress-responsive Markers But Not Nutrition...mentioning
confidence: 99%
“…The increase in ABA may also be induced by water loss resulting from M. usitatus, as ABA is also an indicator of water stress. Li et al [26] have shown that defensive resistance of cowpea control M. usitatus is mediated by JA insect damage. However, there was no significant difference in SA content between treatments.…”
Section: Usitatus Altered Stress-responsive Markers But Not Nutrition...mentioning
confidence: 99%
“…Jasmonic acid (JA) and its derivatives are one of the key groups of “stress” plant hormones [ 3 , 4 , 5 ]. A large body of experimental data has been accumulated showing the action of JA as a regulator of plant growth and development [ 6 , 7 ], as well as signal activating expression of plant defense genes during pathogen infestation [ 8 , 9 ] and plant damage by phytophages [ 10 ]. In recent decades, it has been demonstrated that JA also participates in the adaptive responses of plants to various abiotic factors such as extreme temperatures, drought, salinity, heavy metal ions, and ultraviolet radiation [ 3 , 9 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%